2015
DOI: 10.1108/bepam-03-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Contextualizing learning approaches which shape BIM for maintenance

Abstract: Publisher: Emerald 2Contextualizing learning approaches which shape BIM for maintenance Abstract Purpose: Studies of BIM examine the potential benefits in maintenance. There is also a perspective maintenance teams should be involved early in the building project process.There is little understanding on learning processes for BIM in maintenance in the early building project stage which this paper sets out to address. Methodology:Case study is used to examine the context maintenance learn about BIM.Maintenance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…Built asset proposals can be rigorously analysed across disciplines and organisations. Simulations can be quickly executed and performance benchmarked, enabling improved and innovative solutions [26,75,94,95,96,98] Collaboration between building owners and the FMT at the design stages is very limited. Little evidence shows FM related constraints being analysed in BIM.…”
Section: D (3d + Fm)mentioning
confidence: 99%
“…Built asset proposals can be rigorously analysed across disciplines and organisations. Simulations can be quickly executed and performance benchmarked, enabling improved and innovative solutions [26,75,94,95,96,98] Collaboration between building owners and the FMT at the design stages is very limited. Little evidence shows FM related constraints being analysed in BIM.…”
Section: D (3d + Fm)mentioning
confidence: 99%
“…Deployment of digital modelling in asset management can greatly improve the quality of data transfers between development stakeholders (Jiao et al, 2013;Lindkvist, 2015;Khaddaj and Srour, 2016). Traditional, manual handover of data often leads to inaccuracies (or worse, loss of data), diminishing the operational information held on a building during its lifecycle (Lindkvist, 2015;Motawa and Almarshad, 2015;Love et al, 2016a). Studies have shown that facility owners regularly encounter incomplete as-built data documentation, fostering dissatisfaction, particularly where transferred operations and maintenance (O&M) data proves wholly unsuitable for asset management (Mayo and Issa, 2016).…”
Section: Digital Asset Managementmentioning
confidence: 99%
“…However, academic discourse points toward a disconnect in interoperability related to BIM format data across asset information systems including: computerised maintenance systems (CMMS); energy management systems (EMS); electronic document management systems (EDMS); and building automation systems (BAS) (Becerik-Gerber et al, 2012;Ilter and Ergen, 2015). The primary objective of any data management activity is to enable increased data interoperability, essentially allowing data generated by one party to be easily accessible for all participants (Jiao et al, 2013;Lindkvist, 2015;Khaddaj and Srour, 2016). In practice, and despite the desire for sharing capabilities amongst asset management applications, many existing systems support the individual asset management function for which they were designed, but leave the overall interoperability with other systems in a fragmented stateoften requiring manual input to facilitate any form of exchange (Becerik-Gerber et al, 2012;Counsell, 2012;Xu et al, 2016).…”
Section: Data Interoperabilitymentioning
confidence: 99%
See 2 more Smart Citations